Assessment of difficulty in laparoscopic distal pancreatectomy: A modification of the Japanese difficulty scoring system – A single‐center high‐volume experience. (7th August 2021) - Deiro, Giacomo; De Pastena, Matteo; Paiella, Salvatore; Balduzzi, Alberto; Montagnini, Greta; Andreotti, Elena; Casetti, Luca; Landoni, Luca; Salvia, Roberto; Esposito, Alessandro
Abstract: Background: The Japanese difficulty scoring system (DSS) was developed to assess the difficulty of laparoscopic distal pancreatectomy (LDP). The study aimed to validate a modified DSS (mDSS) in a European high‐volume center. Methods: Patients' clinical data underwent LDP for benign and malignant pancreatic lesion between September 2013 and February 2020 were reviewed. Expert laparoscopic surgeons performed the procedures. The mDSS consisted of seven variables, such as type of operation, malignancy, neoadjuvant therapy, pancreatic resection line, tumor close to major vessels, tumor extension to peripancreatic tissue, and left‐sided portal hypertension and/or splenomegaly. According to the difficulty level and previous score, the mDSS was subdivided into three classes: low, intermediate, and high. Surrogates of case complexity (operative time, intraoperative blood loss and blood transfusion requirements, conversion rate) were used to validate the new scoring system. Results: The study population included 140 LDP. Ninety‐five (68%), 35 (25%) and 10 (7%) patients belonged to low, intermediate, and high difficulty groups. The mDSS identified the complexity of the surgical case of the series for all the surrogates of complexity considered, namely conversion rate ( P = .004), operative time ( P = .033) and intraoperative blood loss ( P = .009). No differences were recorded in the postoperative outcomes ( P > .05). Conclusion: The mDSS for LDP better stratified the pancreatic procedures according to their complexity. The new scoring system may allow an appropriate preoperative evaluation of surgical difficulty, facilitating LDP's training program. Future prospective studies are needed to validate the mDSS. Abstract : Highlight Deiro and colleagues devised and evaluated a new difficulty scoring system to preoperatively assess the complexity of laparoscopic distal pancreatectomy based on the existing Japanese system. The modified difficulty scoring system provides appropriate preoperative assessment of surgical difficulty and facilitates the administration of training programs for laparoscopic distal pancreatectomy.